Immunizations during pregnancy: How, when and why. (September 2019) - Psarris, Alexandros; Sindos, Michael; Daskalakis, Georgios; Chondrogianni, Maria Eleni; Panayiotou, Stefani; Antsaklis, Panagiotis; Loutradis, Dimitrios
Abstract: Maternal immunization during pregnancy provide protection for the mother and the fetus against certain pathogens. Immunizations during pregnancy are divided to routine immunizations recommended for all pregnant women, immunizations for certain medical indications and vaccines that are potentially harmful during pregnancy and should be avoided. We conducted a comprehensive review of the literature regarding immunizations during pregnancy. The search terms used were immunization, vaccine, pregnancy, influenza, pertussis, safety and efficacy. We gathered all available guidelines on vaccination during pregnancy. Generally, vaccines are allowed during pregnancy when the benefits outweigh the risks. Tdap and inactivated flu vaccines are routinely recommended during pregnancy. Vaccines containing live attenuated viruses are contraindicated during pregnancy. These are LAIV influenza, MMR, Varicella, Zoster, BCG and smallpox pre-exposure. All other vaccines are given when medically indicated and the possible benefits outweigh the risks. Obstetricians and gynecologists should be familiar with the indications of vaccination during pregnancy. Vaccination coverage of pregnant women with routinely recommended vaccines has increased but further efforts are needed. Our aim is to review vaccination practices during pregnancy, demonstrate the benefits and dangers of different vaccines, evaluate their effectiveness and define the proper timing of vaccination.